Evaluasi Program Teaching Factory terhadap Kompetensi Pedagogik Guru Mata Pelajaran Produktif SMKN 1 Tanjung Menggunakan Model Kirkpatrick - Rizza Maria Ulfa; Sy. Mawaddah Al Idrus; Ni Luh Tri Dewi Damayanti; Widi Ikhtiari Ahmad; Muhammad Muhammad; Candra Candra (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to evaluate the implementation of the Teaching Factory (TeFa) program in relation to the pedagogical competence of productive subject teachers at SMKN 1 Tanjung using the Kirkpatrick evaluation model. This study employed a qualitative approach through observation, interviews, and documentation. The results indicate that the teaching factory program encourages changes in learning practices toward a more contextual, authentic, and experience-based approach. However, these changes have not been consistently implemented due to limitations at the individual teacher level and institutional support. Evaluation based on the Kirkpatrick model indicates that the program's impact is strongest at the level of reactions and learning, but not yet optimal at the level of behavior and outcomes. These findings confirm that the implementation of the teaching factory has not been fully internalized in daily learning practices. This study concludes that the success of the teaching factory program is not solely determined by the program design but is highly dependent on teachers' reflective ability to continuously reconstruct their pedagogical practices.